Curable resin composition, film and prepreg
Patent Information
- Application Number
- JP2024147170
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-03-11
AI Technical Summary
【0009】 本発明の多官能ビニル芳香族共重合体、架橋剤、ラジカル重合開始剤を含む組成物からは耐熱性、相溶性、誘電特性が改善された硬化物が得られる。更に、これらの組成物かられたフィルム、プリプレグは耐熱性、相溶性、誘電特性に優れた製品を得ることができる。
Smart Images

Figure 2025032067000001 
Figure 2025032067000002 
Figure 2025032067000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable resin composition containing a novel polyfunctional vinyl aromatic copolymer having improved heat resistance, compatibility, dielectric properties, wet heat reliability and thermal oxidative degradation resistance. In particular, the present invention relates to a curable resin composition that can be suitably used as an electrical insulating material for printed circuit boards, electronic components, and the like. [Background technology]
[0002] In recent years, the amount of information and communication has increased, and information and communication in the high frequency band has become more common. In order to reduce transmission loss in the high frequency band, there is a demand for electrical insulating materials with better electrical properties, particularly low dielectric constants and low dielectric loss tangents. Furthermore, printed circuit boards and electronic components using such electrical insulating materials are exposed to high-temperature solder reflow during mounting, so materials with high heat resistance, i.e., high glass transition temperatures, are required. In particular, due to environmental concerns, lead-free solders with high melting points are now being used, and there is an increasing demand for electrical insulating materials with higher heat resistance. In response to these demands, cured resins using vinyl compounds with various chemical structures have been proposed.
[0003] Patent Document 1 discloses a polyfunctional vinyl aromatic copolymer having structural units derived from a divinyl aromatic compound, a monovinyl aromatic compound, and an olefin-based compound containing an aromatic condensed ring structure as a soluble polyfunctional resin. However, since the material disclosed in Patent Document 1 is mainly considered for use in diene rubbers used in automobile tires, it is considered difficult to achieve both heat resistance and a low dielectric tangent when used alone as an electronic material for the recent increase in communication speed.
[0004] Patent Document 2 discloses a curable resin composition composed of an olefin-aromatic vinyl compound-aromatic polyene copolymer and, as an additive resin, one or more selected from the group consisting of a hydrocarbon-based elastomer, polyphenylene ether, an olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer, and an aromatic polyene resin. However, the olefin-aromatic vinyl compound-aromatic polyene copolymer disclosed in Patent Document 2 contains many ethylene units as an olefin structure, so that the glass transition temperature is low and the heat resistance is poor. In order to improve this heat resistance, an additive resin is added, but the amount of the additive resin is increased to achieve the improvement effect, and the low dielectric tangent, which is a characteristic of the olefin-aromatic vinyl compound-aromatic polyene copolymer, is impaired. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO2020 / 067336 [Patent Document 2] Patent No. 2024-71737 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a curable resin composition containing a polyfunctional vinyl aromatic copolymer that has excellent heat resistance and compatibility and can give a cured product or molded article having improved dielectric properties, particularly dielectric tangent. [Means for solving the problem]
[0007] That is, the present invention provides (A) Multifunctional vinyl aromatic copolymer (B) Crosslinking agent (C) Radical polymerization initiator The polyfunctional vinyl aromatic copolymer as component (A) satisfies all of the following conditions (1) to (4), and the curable resin composition is characterized in that, when the resin solid content in the resin composition is 100 parts by weight, the amount of component (A) is 5 to 95 parts by weight, the amount of component (B) is 5 to 95 parts by weight, and the amount of component (C) is 0.01 to 10 parts by weight relative to 100 parts by weight of the resin solid content. (1) containing 0.5 mol % or more and 95 mol % or less of structural units derived from a divinyl aromatic compound (a), 0.5 mol % or more and 75 mol % or less of structural units derived from a monovinyl aromatic compound (b) having no substituent at the α-position, and 5 mol % or more and 75 mol % or less of structural units derived from an α,α-disubstituted olefin compound (c); (2) the number average molecular weight Mn of the polyfunctional vinyl aromatic copolymer is 300 to 100,000, and the molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight Mw to the number average molecular weight Mn is 100 or less; (3) The monovinyl aromatic compound (b) having no substituent at the α-position is one or more monomers selected from the group consisting of styrene, vinylnaphthalene, vinylbiphenyl, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, m-ethylvinylbenzene, and p-ethylvinylbenzene; (4) The α,α-disubstituted olefin compound (c) is one or more monomers selected from the group consisting of isobutylene, diisobutylene, 2-methyl-1-butene, 2-methyl-1-pentene, 1-methyl-1-cyclopentene, 2-methyl-1-hexene, 1-methyl-1-cyclohexene, 2-methyl-1-heptene, 2-methyl-1-octene, 2-methyl-1-nonene, 2-methyl-1-decene, 2-methyl-1-dodecene, 2-methyl-1-tetradecene, 2-methyl-1-hexadecene, 2-methyl-1-octadecene, 2-methyl-1-eicosene, 2-methyl-1-docosene, 2-methyl-1-tetracosene, and α-methylstyrene.
[0008] The curable resin composition of the present invention suitably contains a maleimide structure as a component that causes a crosslinking reaction in the crosslinking agent, which is component (B). In the curable resin composition of the present invention, it is preferable that the crosslinking agent, which is the component (B), contains a polyphenylene ether structure. In the curable resin composition of the present invention, it is preferable that the crosslinking agent, which is the component (B), contains a structure derived from a butadiene structure. In the curable resin composition of the present invention, the radical polymerization initiator as component (C) preferably contains a peroxide structure.The radical polymerization initiator as component (C) preferably contains an azo structure. The curable resin composition of the present invention preferably has a dielectric loss tangent after curing of less than 0.005 at 10 GHz. The curable resin composition of the present invention may be in the form of a varnish, containing a solvent in addition to the components (A), (B), and (C). The present invention relates to a film made of a curable resin composition, and a prepreg in which a glass cloth is impregnated with the curable resin composition. Effect of the Invention
[0009] The composition containing the polyfunctional vinyl aromatic copolymer, the crosslinking agent, and the radical polymerization initiator of the present invention can provide a cured product having improved heat resistance, compatibility, and dielectric properties. Furthermore, the film and prepreg made from these compositions can provide products having excellent heat resistance, compatibility, and dielectric properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The polyfunctional vinyl aromatic copolymer used in the present invention contains 0.5 mol % or more and 95 mol % or less of structural units derived from a divinyl aromatic compound (a), 0.5 mol % or more and 75 mol % or less of structural units derived from a monovinyl aromatic compound (b) having no substituent at the α-position, and 5 mol % or more and 75 mol % or less of structural units derived from an α,α-disubstituted olefin compound (c).
[0011] The divinyl aromatic compound (a) plays a role in forming a branched structure to impart multifunctionality, and also plays a role as a crosslinking component to impart heat resistance when the resulting soluble multifunctional vinyl aromatic copolymer is heat cured. [ka] Examples of the divinyl aromatic compound (a) are not limited as long as they are aromatic compounds having two vinyl groups, but divinylbenzene (including each positional isomer or a mixture thereof), divinylnaphthalene (including each positional isomer or a mixture thereof), and divinylbiphenyl (including each positional isomer or a mixture thereof) are preferably used. These can be used alone or in combination of two or more kinds. From the viewpoint of moldability, divinylbenzene (m-isomer, p-isomer, or a mixture of these positional isomers) is more preferable.
[0012] The structural unit derived from the divinylaromatic compound (a) may be contained in an amount of 0.5 mol % or more and 95 mol % or less with respect to the total of the structural units derived from (a), (b) and (c) being 100 mol %. It is preferably 1 mol % or more, more preferably 5 mol % or more. The structural unit derived from the divinylaromatic compound (a) may have a plurality of structures such as a structure in which two vinyl groups are reacted with only one or two vinyl groups are reacted, but it is preferable that the structural unit contains 0.5 to 95 mol % of a repeating unit in which only one vinyl group is reacted. It is more preferably 5 to 70 mol %, further preferably 10 to 60 mol %, and particularly preferably 15 to 50 mol %. By making it 0.5 to 95 mol %, it has a low dielectric tangent, high toughness, excellent heat resistance, and excellent compatibility with other resins. In addition, when it is made into a resin composition, it has excellent moist heat resistance, thermal oxidation deterioration resistance, and molding processability. If it is less than 0.5 mol %, the heat resistance tends to decrease, whereas if it exceeds 95 mol %, the interlayer peel strength when formed into a laminate tends to decrease.
[0013] The monovinyl aromatic compound (b) having no substituent at the α-position is not particularly limited as long as it is a compound having a vinyl group directly bonded to an aromatic ring, but a compound represented by formula (b) is preferred. [ka] (Ar is an aromatic hydrocarbon group having 6 to 30 carbon atoms)
[0014] The aromatic hydrocarbon group having 6 to 30 carbon atoms is not particularly limited, and examples thereof include those in which one hydrogen atom has been removed from a monocyclic aromatic compound such as benzene, furan, pyrrole, thiophene, imidazole, pyrazole, oxazole, isoxazole, thiazole, isothiazole, pyridine, pyrimidine, pyridazine, pyrazine, or triazine, and those in which one hydrogen atom has been removed from a condensed ring aromatic compound such as naphthalene, anthracene, phenalene, phenanthrene, quinoline, isoquinoline, quinazoline, phthalazine, pteridine, coumarin, indole, benzimidazole, benzofuran, or acridine. A combination of two or more of these aromatic compounds may be used, and examples thereof include compounds in which two hydrogen atoms have been removed from ring-assembly aromatic compounds such as biphenyl, binaphthalene, bipyridine, bithiophene, phenylpyridine, phenylthiophene, terphenyl, diphenylthiophene, and quaterphenyl. Preferred are benzene, naphthalene, biphenyl and anthracene.
[0015] The structural unit derived from the monovinyl aromatic compound (b) having no substituent at the α-position is 0.5 mol% or more and 75 mol% or less, preferably 10 mol% to 60 mol%, based on 100 mol% of the total of the structural units derived from (a), (b), and (c). If it is less than 0.5 mol%, heat resistance is not exhibited, and if it exceeds 75 mol%, the number of monomer units derived from other components, particularly the divinyl aromatic compound (a), is reduced, making it difficult to cause a crosslinking reaction and not exhibiting curability.
[0016] The aromatic hydrocarbon group having 6 to 30 carbon atoms may have a substituent, and examples of such substituents include hydrocarbon groups such as methyl, ethyl, propyl, and butyl groups, alkoxyl groups such as methoxy and ethoxy groups, substituents containing a carbonyl structure such as acetyl groups, and substituents containing an ester structure such as acetoxy groups. Among these substituents, preferred are hydrocarbon groups, and particularly preferred are ethyl groups, in terms of reactivity and the fact that the dielectric loss tangent is not large.
[0017] The α,α-disubstituted olefin compound (c) used in the present invention is one or more selected from the group consisting of isobutylene, diisobutylene, 2-methyl-1-butene, 2-methyl-1-pentene, 1-methyl-1-cyclopentene, 2-methyl-1-hexene, 1-methyl-1-cyclohexene, 2-methyl-1-heptene, 2-methyl-1-octene, 2-methyl-1-nonene, 2-methyl-1-decene, 2-methyl-1-dodecene, 2-methyl-1-tetradecene, 2-methyl-1-hexadecene, 2-methyl-1-octadecene, 2-methyl-1-eicosene, 2-methyl-1-docosene, 2-methyl-1-tetracosene, and α-methylstyrene, and diisobutylene is preferred because of its excellent reactivity and dielectric loss tangent.
[0018] The α,α-disubstituted olefin compound (c) is produced by adding the α,α-disubstituted olefin to the terminal of the compound having the structure represented by formula (c1) or (c2). [ka] (R 1 is a hydrocarbon group having 1 to 25 carbon atoms) [ka] (R 1 is a hydrocarbon group having 1 to 25 carbon atoms) This is due to the reactivity of the growing end derived from the α,α-disubstituted olefin compound (c), and it is considered that the structure of the growing end generated by the α,α-disubstituted olefin compound (c) added to the growing end is unstable, so the termination reaction occurs preferentially over the polymerization reaction to other vinyl compounds. The structural unit derived from this olefin compound (c) is contained in an amount of 5 mol% or more and 75 mol% or less with respect to the total of the structural units derived from (a), (b) and (c) being 100 mol%. If it contains 75 mol% or more, the molecular weight is not sufficiently extended, and many branched structures are formed, and other monomer components, especially divinyl aromatic compounds, are not introduced, so that curability is not expressed. On the other hand, if it is less than 5 mol%, the molecular weight is too large, which causes the viscosity to increase and the amount of the α,α-disubstituted olefin compound (c) with low polarity to decrease relatively, resulting in poor dielectric properties.
[0019] The polyfunctional vinyl aromatic copolymer used in the present invention has a number average molecular weight (Mn: number average molecular weight in terms of standard polystyrene measured using gel permeation chromatography) of preferably 300 to 100,000, more preferably 400 to 50,000, and even more preferably 500 to 10,000. If Mn is less than 300, the amount of monofunctional copolymer components contained in the polyfunctional vinyl aromatic copolymer increases, so that the heat resistance of the cured product tends to decrease, while if Mn is more than 100,000, gel tends to be generated and the viscosity increases, so that the moldability tends to decrease. In addition, the value of the molecular weight distribution (Mw / Mn), which is expressed by the ratio of the weight average molecular weight (Mw: weight average molecular weight in terms of standard polystyrene measured using gel permeation chromatography) to Mn, is 100 or less, preferably 50 or less, more preferably 1.5 to 30, and most preferably 2.0 to 20. If Mw / Mn exceeds 100, gel tends to occur in the product, and further, the viscosity of the polyfunctional vinyl aromatic copolymer increases, tending to deteriorate the molding processability.
[0020] The polyfunctional vinyl aromatic copolymer is soluble in any of the following solvents: toluene, xylene, tetrahydrofuran, methyl ethyl ketone, dichloroethane or chloroform, and preferably in any of the above solvents.To be a polyfunctional copolymer that is soluble in a solvent, it is necessary that a part of the vinyl group of divinylbenzene remains uncrosslinked and has an appropriate degree of crosslinking.Here, soluble in a solvent means that the soluble polyfunctional vinyl aromatic copolymer dissolves in 100g of the above solvent at 5g or more, more preferably dissolves in 30g or more, and particularly preferably dissolves in 50g or more.
[0021] Next, a method for producing the polyfunctional vinyl aromatic copolymer used in the present invention will be described. The polyfunctional vinyl aromatic copolymer can be easily produced by the following production method. The production method is a method for producing a polyfunctional vinyl aromatic copolymer by polymerizing a divinyl aromatic compound (a), a vinyl aromatic compound (b) having no substituent at the α-position, and an α,α-disubstituted olefin compound (c) in the presence of a Lewis acid catalyst at a temperature of -20 to 120°C, and it is preferable to use 0.5 mol% to 95 mol% of the divinyl aromatic compound (a), 0.5 mol% to 75 mol% of the vinyl compound (b) having no substituent at the α-position, and 5 mol% to 75 mol% of the α,α-disubstituted olefin compound (c) relative to the total of (a), (b), and (c).
[0022] The Lewis acid catalyst is a compound consisting of a metal ion (acid) and a ligand (base), and can be used without any particular limitation as long as it can accept an electron pair. Among them, from the viewpoint of the thermal decomposition resistance of the obtained soluble polyfunctional vinyl aromatic copolymer, metal fluorides or complexes thereof are preferred, and in particular, divalent to hexavalent metal fluorides, chlorides, or complexes thereof such as B, Al, Ga, In, Si, Ge, Sn, Pb, Sb, Bi, Ti, W, Zn, Fe, and V are preferred. These catalysts can be used alone or in combination of two or more. From the viewpoint of the control of the molecular weight and molecular weight distribution of the obtained soluble polyfunctional vinyl aromatic copolymer and the polymerization activity, boron trifluoride ether complexes, titanium chloride, and tin chloride are suitable, and further, boron trifluoride ether complexes are most preferably used. Here, examples of the ether complexes include diethyl ether and dimethyl ether. The Lewis acid catalyst is preferably used in the range of 0.001 to 100 moles, more preferably 0.01 to 50 moles, relative to 100 moles of the total of all monomer components. Most preferably 0.1 to 10 moles. If it exceeds 100 moles, the polymerization rate becomes too high, making it difficult to control the molecular weight distribution. If it is less than 0.001 moles, the polymerization rate becomes too low, resulting in an increase in costs and making it unsuitable for industrial implementation.
[0023] In the method for producing a polyfunctional vinyl aromatic copolymer of the present invention, a compound having a hydroxyl group can be used as a co-catalyst. It is believed that the reaction proceeds when the compound having a hydroxyl group reacts with a Lewis acid catalyst, resulting in the elimination of the hydroxyl group and the generation of a cation. Examples of compounds having a hydroxyl group include methanol, ethanol, 1-propanol, 2-propanol, n-butanol, tertiary butanol, benzyl alcohol, 1-phenylethanol, and 1-phenylpropanol. Among these, 1-phenylethanol and 1-phenylpropanol are preferably used because of their stability in reactivity. These compounds are preferably used in an amount of 0.1 to 10 times by molar relative to the Lewis acid catalyst, and more preferably in an amount of 1 to 8 times by molar. If the amount is less than 0.1 times by molar, there is no catalytic effect, and if the amount is more than 10 times by molar, the reaction does not proceed stably.
[0024] In the method for producing a polyfunctional vinyl aromatic copolymer of the present invention, one or more Lewis base compounds can be used as a cocatalyst. Specific examples of the Lewis base compound include the following compounds. 1) Ester compounds such as ethyl acetate, propyl acetate, butyl acetate, phenyl acetate, and methyl propionate, 2) Thioester compounds such as methyl mercaptopropionic acid and ethyl mercaptopropionic acid, 3) Ketone compounds such as methyl ethyl ketone, methyl isobutyl ketone, and benzophenone 4) Methylamine, ethylamine, propylamine, butylamine, cyclohexylamine amine, methylethylamine, dimethylamine, diethylamine, dipropylamine, Djiboutiamine amine compounds such as amines, 5) Ether compounds such as diethyl ether and tetrahydrorane, 6) Thioether compounds such as diethyl sulfide and diphenyl sulfide, and 7) Phosphine compounds such as tripropylphosphine, tributylphosphine, trihexylphosphine, tricyclohexylphosphine, trioctylphosphine, vinylphosphine, propenylphosphine, cyclohexenylphosphine, dialkenylphosphine, and trialkenylphosphine. Among these, one or more compounds selected from the group consisting of ester compounds, ketone compounds, ketone compounds, and ether compounds are preferred, and ester compounds and ketone compounds are more preferred, because they act synergistically with the Lewis acid catalyst to easily control the polymerization rate and the molecular weight distribution of the polymer. These Lewis base compounds can be used alone or in combination.
[0025] The amount of the co-catalyst such as a Lewis base compound is preferably 0.1 to 1000 mol, more preferably 1.0 to 500 mol, and particularly preferably 10 to 200 mol, relative to 100 mol of the total of all monomer components. Within the above range, the polymerization rate is appropriately maintained and at the same time, the selectivity of the reaction between monomers is improved, resulting in excellent productivity, suppressing excessive increase or decrease in molecular weight, and providing a polyfunctional vinyl aromatic copolymer with excellent moldability.
[0026] In this polymerization reaction, a solvent can be added as necessary. The solvent is a compound that does not essentially inhibit cationic polymerization, and dissolves the Lewis acid catalyst, the cocatalyst, the monomer components, and the soluble polyfunctional vinyl aromatic copolymer produced to form a homogeneous solution. An aromatic organic solvent having a dielectric constant in the range of 2 to 15 is preferable, and can be used alone or in combination of two or more kinds. If the dielectric constant of the solvent is less than 2, the molecular weight distribution becomes broad, which is not preferable, and if it exceeds 15, the polymerization rate decreases.
[0027] As the organic solvent, from the viewpoint of the balance between polymerization activity and solubility, aromatic compounds are preferable, and toluene and xylene are particularly preferable. This is because in the polymerization reaction, after an olefin compound is added to the polymerization terminal, an addition reaction to the aromatic compound occurs and a termination reaction occurs. Since this reaction is necessary for controlling the molecular weight, the amount of the solvent used is determined so that the concentration of the copolymer in the polymerization solution at the end of the polymerization is 1 to 90 wt%, preferably 10 to 80 wt%, and particularly preferably 20 to 70 wt%, taking into consideration the viscosity of the obtained polymerization solution and the ease of heat removal. If this concentration is less than 1 wt%, the polymerization efficiency is low, leading to an increase in costs, and if it exceeds 90 wt%, the molecular weight and molecular weight distribution of the functionalized vinyl aromatic copolymer produced will increase, leading to a decrease in moldability.
[0028] When producing a polyfunctional vinyl aromatic copolymer, it is necessary to polymerize the monomers (a), (b) and (c) at a temperature of -20 to 120°C. The temperature is preferably 0 to 110°C. The temperature is particularly preferably 30 to 90°C. If the polymerization temperature exceeds 120°C, the selectivity of the reaction decreases, resulting in problems such as an increase in molecular weight distribution and the generation of gel. If the polymerization is carried out at a temperature lower than -20°C, the catalytic activity decreases significantly, making it necessary to add a large amount of catalyst.
[0029] After the polymerization reaction is stopped, the method for recovering the polyfunctional vinyl aromatic copolymer is not particularly limited, and for example, a commonly used method such as a heat concentration method, a vacuum concentration method, a steam stripping method, or precipitation in a poor solvent may be used.
[0030] The polyfunctional vinyl aromatic copolymer obtained by the above-mentioned production method has a structure containing 0.5 mol% or more and 95 mol% or less of structural units derived from a divinyl aromatic compound (a), 0.5 mol% or more and 75 mol% or less of structural units derived from a monovinyl aromatic compound (b) having no substituent at the α-position, and 5 mol% or more and 75 mol% or less of structural units derived from an α,α-disubstituted olefin compound (c). It has an Mn of 300 to 100,000, an Mw / Mn of 100 or less, and is soluble in toluene, xylene, tetrahydrofuran, dichloroethane, or chloroform.
[0031] The crosslinking agent used in the present invention contains one or more functional groups that react with vinyl groups. As the functional group that can react with vinyl groups, those having a carbon-carbon double bond or a carbon-carbon triple bond are used. Among these, compounds having structures represented by formula (e) and formula (f) are particularly useful. In addition, it is desirable to contain two or more functional groups that react with vinyl from the viewpoint of initiating a crosslinking reaction. [ka] [ka]
[0032] An example of a compound having formula (e) is a resin having a polybutadiene structure. Polybutadiene is produced by polymerization of butadiene, and by adjusting the production conditions, the structure becomes a mixture of 1,4-adducts and 1,2-adducts. Of these, formula (e) is formed by 1,2-addition. In addition, examples of resins using butadiene include not only butadiene homopolymerization but also styrene-butadiene-styrene block copolymers (SBS) and styrene-ethylene-butadiene-styrene copolymers (SEBS), and the crosslinking agent of the present invention preferably contains two or more of formula (e) per molecular weight.
[0033] Compounds having formula (f) are generally classified as maleimide resins. Maleimide resins may have one or more maleimide groups, but it is preferable to have two or more maleimide groups in order to cause a crosslinking reaction. Maleimide resins are synthesized from amino groups and maleic anhydride, but there are no particular limitations on the compounds having amino groups used as raw materials.
[0034] As the crosslinking agent, a compound having a functional group reactive with a vinyl group and the following polyphenylene ether structure can be used. [ka] These compounds have excellent heat resistance and electrical reliability, and their rigid structure is expected to improve mechanical properties. These compounds have carbon-carbon double bonds at the end or side chain that react with vinyl groups, and can form crosslinked structures by reacting with polyfunctional vinyl aromatic copolymers. Examples of functional groups that react with vinyl groups include styryl groups, vinyl ether groups, acrylic groups, methacrylic groups, and the maleimide group mentioned above.
[0035] The radical polymerization initiator used in the present invention is one that generates radicals by decomposition due to heat, light, etc. The radicals generated by heat, light, etc. react with the double bonds contained in the polyfunctional vinyl aromatic copolymer (A) and the crosslinking agent (B) to form a crosslinked structure. As the radical polymerization initiator, known substances are used. Representative examples include peroxides such as benzoyl peroxide, cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, di-t-butyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, dicumyl peroxide, di-t-butylperoxyisophthalate, t-butylperoxybenzoate, 2,2-bis(t-butylperoxy)butane, 2,2-bis(t-butylperoxy)octane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, di(trimethylsilyl)peroxide, trimethylsilyltriphenylsilylperoxide, and the like, 2,2'-azobis[N- (2-carboxyethyl)-2-methylpropionamidine] tetrahydrate, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2'-azobis[2-(2-imidazolin-2-yl)propane], dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis(N-butyl-2-methylpropionamide) ), 1,1'-azobis(cyclohexane-1-carbonitrile), dimethyl 1,1'-azobis(1-cyclohexanecarboxylate), 2,2'-azobis(isobutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), and other azo compounds, but are not limited to these. Although not a peroxide or azo compound, 2,3-dimethyl-2,3-diphenylbutane can also be used as a radical polymerization initiator (h). Among these, α,α'-bis(t-butylperoxy-m-isopropyl)benzene and 2,2'-azobis(2,4,4-trimethylpentane) are preferably used. α,α'-bis(t-butylperoxy-m-isopropyl)benzene has a relatively high reaction initiation temperature. Therefore, it is possible to suppress the promotion of the curing reaction at the time when curing is not required, such as when drying the prepreg, and to suppress the deterioration of the storage stability of the curable resin composition of the present invention. Furthermore, since α,α'-bis(t-butylperoxy-m-isopropyl)benzene has low volatility, it does not volatilize during drying or storage of the prepreg, and has good stability. Since the generated radical species of 2,2'-azobis(2,4,4-trimethylpentane) are composed only of hydrocarbons, a cured product having excellent dielectric properties, particularly a dielectric loss tangent, can be obtained. These radical polymerization initiators may be used alone or in combination of two or more kinds.
[0036] The amount of the radical polymerization initiator (C) is preferably in the range of 0.01 to 10 parts by weight, more preferably in the range of 0.1 to 8 parts by weight, based on 100 parts by weight of the resin component consisting of the polyfunctional vinyl aromatic copolymer (A) and the crosslinking agent (B). Within this range, the reaction proceeds well without impeding the curing reaction. If it is more than 10 parts by weight, the curing reaction is too fast and voids are likely to occur in the cured product. If it is less than 0.1 part by weight, the curing reaction does not proceed sufficiently, resulting in poor curing and making it impossible to form a molded product.
[0037] The curable resin composition of the present invention can be made into a varnish-like state by using a solvent during mixing. The solvent used here can be a commonly used organic solvent. For example, ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, esters such as ethyl acetate, propyl acetate, and butyl acetate, aprotic polar solvents such as dimethylacetamide, dimethylformamide, and N-methyl-2-pyrrolidone, and aromatic hydrocarbon solvents such as toluene and xylene can be used alone or in combination of two or more. Among these solvents, aromatic hydrocarbons such as benzene, toluene, and xylene are preferred from the viewpoint of dielectric properties.
[0038] Known thermoplastic resins can be blended in the present invention. The thermoplastic resins described here do not contain functional groups that react with vinyl groups. Examples of thermoplastic resins that do not contain functional groups that react with vinyl groups include polystyrene, polyetherimide resins, polyethersulfone resins, PPS resins, polycyclopentadiene resins, polycycloolefin resins, and known thermoplastic elastomers, such as styrene-ethylene-propylene copolymers, styrene-ethylene-butylene copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, hydrogenated styrene-butadiene copolymers, and hydrogenated styrene-isoprene copolymers that do not contain 1,2 adducts, and rubbers, such as polybutadiene and polyisoprene. In addition, one or more of these thermoplastic resins may be blended at the same time.
[0039] The curable resin composition of the present invention may contain a known flame retardant. The flame retardant can further increase the flame retardancy of the cured product of the curable resin composition. The flame retardant is not particularly limited. Specifically, in fields where halogen-based flame retardants such as bromine-based flame retardants are used, for example, ethylene dipentabromobenzene, ethylene bis tetrabromoimide, decabromodiphenyl oxide, and tetradecabromodiphenoxybenzene, which have a melting point of 300°C or more, are preferred. It is believed that the use of a halogen-based flame retardant can suppress the elimination of halogen at high temperatures and suppress the decrease in heat resistance. In addition, in fields where halogen-free is required, phosphate ester flame retardants, phosphazene flame retardants, and phosphinate flame retardants are examples. A specific example of a phosphate ester flame retardant is a condensed phosphate ester of dixylenyl phosphate. A specific example of a phosphazene flame retardant is phenoxyphosphazene. A specific example of a phosphinate flame retardant is a metal phosphinate of aluminum dialkylphosphinate. Each of the exemplified flame retardants may be used alone or in combination of two or more kinds.
[0040] The curable resin composition of the present invention can be blended with a known filler. Examples of fillers include those added to enhance the heat resistance and flame retardancy of the cured product of the curable resin composition, and are not particularly limited. In addition, by including a filler, the heat resistance and flame retardancy can be further enhanced. Specifically, silica such as spherical silica, metal oxides such as alumina, titanium oxide, and mica, metal hydroxides such as aluminum hydroxide and magnesium hydroxide, talc, aluminum borate, barium sulfate, and calcium carbonate can be mentioned. Among these, silica, mica, and talc are preferred, and spherical silica is more preferred. In addition, one of these may be used alone, or two or more may be used in combination. In addition, it may be used as it is, or it may be surface-treated with a silane coupling agent such as an epoxy silane type or an amino silane type. As the silane coupling agent, from the viewpoint of reactivity with a radical polymerization initiator, vinyl silane type, methacryloxy silane type, acryloxy silane type, and styryl silane type silane coupling agents are preferred. This increases the adhesive strength to the metal foil and the interlayer adhesive strength between resins. Also, instead of a method of previously treating the surface of the filler, the silane coupling agent may be added by integral blending. The content of the filler is preferably 10 to 200 parts by mass, and more preferably 30 to 150 parts by mass, per 100 parts by mass of the total of the organic components such as monomers and the flame retardant.
[0041] The curable resin composition of the present invention may further contain additives other than the flame retardant and the filler, such as antifoaming agents such as silicone-based antifoaming agents and acrylic acid ester-based antifoaming agents, heat stabilizers, antistatic agents, ultraviolet absorbers, dyes and pigments, lubricants, and dispersants such as wetting dispersants.
[0042] The curable resin composition of the present invention can be formed into a film, which is one form of the curable resin composition of the present invention, by forming the curable resin composition into a film shape. The thickness of the film is not particularly limited, but is preferably in the range of 3 to 200 μm, more preferably 5 to 100 μm. The method for producing the film of the present invention is not particularly limited, and examples thereof include a method in which the curable resin composition is uniformly dissolved or dispersed in an aromatic solvent, ketone solvent, or a mixture thereof, and then coated on a resin film such as a PET film, followed by drying. Coating can be repeated multiple times as necessary, and in this case, coating can be repeated using multiple solutions with different compositions and concentrations, and finally, the desired resin composition and resin amount can be adjusted.
[0043] The curable resin composition of the present invention can be impregnated into a substrate (prepreg substrate) and dried to produce a prepreg, which is one form of the curable resin composition of the present invention. The prepreg of the present invention can be obtained, for example, by applying (e.g., impregnating or coating) the curable resin composition of the present invention to a substrate, and then semi-curing by heating (e.g., drying at 120 to 220°C for 2 to 15 minutes, etc.). In this case, the amount of the resin composition attached to the substrate, i.e., the amount of the resin composition (including the filler) relative to the total amount of the prepreg after semi-curing, is preferably in the range of 20 to 99 mass%.
[0044] The substrate is not particularly limited as long as it is a substrate used in various printed wiring board materials. Examples of the substrate material include glass fibers (e.g., E glass, D glass, L glass, S glass, T glass, Q glass, UN glass, NE glass, spherical glass, etc.), inorganic fibers other than glass (e.g., quartz, etc.), and organic fibers (e.g., polyimide, polyamide, polyester, liquid crystal polyester, etc.). The form of the substrate is not particularly limited, and includes substrates composed of layered fibers such as woven fabric, nonwoven fabric, roving, chopped strand mat, and surfacing mat. In particular, substrates composed of long fibers such as glass cloth are preferred. Here, long fibers refer to, for example, those having a number average fiber length of 6 mm or more. These substrates can be used alone or in combination of two or more. Among these substrates, from the viewpoint of dimensional stability, woven fabrics that have been subjected to ultra-opening treatment and clogging treatment are preferred, from the viewpoint of moisture absorption and heat resistance, glass woven fabrics that have been surface-treated with a silane coupling agent such as epoxy silane treatment or amino silane treatment are preferred, and from the viewpoint of electrical properties, low-dielectric glass cloths made of glass fibers exhibiting low dielectric constant and low dielectric loss tangent such as L-glass, NE-glass, Q-glass, etc. The thickness of the substrate is not particularly limited and may be, for example, about 0.01 to 0.19 mm. EXAMPLES
[0045] The present invention will now be described with reference to examples, but the present invention is not limited thereto. In each example, all parts are by weight. The physical properties in the examples were measured by the methods shown below.
[0046] 1) Polymer molecular weight and molecular weight distribution The molecular weight and molecular weight distribution of the polymer were measured using a Tosoh HLC-8320GPC with tetrahydrofuran as the solvent, a flow rate of 1.0 ml / min, a column temperature of 40° C., and a calibration curve based on monodisperse polystyrene. 2) Glass transition temperature (Tg) of the cured product The glass transition temperature was measured using a DMA three-point bending mode on a sample piece molded to approximately 2 mm square using the cured product obtained from the examples. The measurement conditions were a nitrogen gas flow, 20°C-200°C, a heating rate of 10°C / min, and a frequency of 1 Hz, and the glass transition temperature was calculated from the peak value of tan δ. The glass transition temperature was evaluated as 150°C or higher as "◎", 100°C or higher but less than 150°C as "〇", and less than 100°C as "×". 3) Monomer consumption rate Quantitative analysis was performed using a Shimadzu GC-2014 (general-purpose gas chromatography) with a capillary column by the internal standard method. The monomer consumption rate was calculated from the difference between the initial and final reaction times, and the mole percentage was calculated from the total amount of monomer consumed. 4) Dielectric properties of the cured product The dielectric properties were evaluated using the cured products obtained from the examples. The measuring equipment used was a Keysight Technologies network analyzer (E8363C) as the network analyzer and split post dielectric resonators (SPDR) as the resonators, and measurements were performed in a 23°C / 50% humidity environment. The dielectric properties of the dielectric loss tangent (Df) at 10 GHz were evaluated as follows: less than 0.002 was marked with "◎", 0.002 or more but less than 0.003 was marked with "◯", 0.003 or more but less than 0.005 was marked with "△", and 0.005 or more was marked with "X".
[0047] Crosslinker A: Styryl-modified polyphenylene ether (polyphenylene ether resin with styryl-modified ends / St-PPE) [ka] Crosslinking agent B: SEBS resin obtained from styryl-modified polyphenylene ether (styrene-ethylene-butadiene-styrene block polymer containing 1,2-adduct of butadiene: structural formula below) [ka] Crosslinker C: Bismaleimide resin (BMI-3000, Designer Molecules) [ka] Radical polymerization initiator: Perbutyl P (α,α'-bis(t-butylperoxy-m-isopropyl)benzene) [ka] Radical polymerization initiator: VR-110 (2,2'-azobis(2,4,4-trimethylpentane)) [ka]
[0048] Synthesis Example 1 Synthesis of polyfunctional vinyl aromatic copolymer A DVB-630 (mixture of divinylbenzene and ethylvinylbenzene, divinylbenzene:ethylvinylbenzene = 0.63:0.37, manufactured by Nippon Steel Chemical & Material Co., Ltd.) 120 g, [ka] 117g styrene, [ka] Diisobutylene (mixture of isomers) 156g, [ka] 14 g of n-propyl acetate and 107 g of toluene were placed in a 1 L reactor, and 2.8 mL of boron trifluoride diethyl ether complex was added at 70° C. and reacted for 2.5 hours. After the polymerization solution was stopped with an aqueous solution of sodium bicarbonate, the oil layer was washed three times with pure water and the polyfunctional vinyl aromatic copolymer A was recovered by degassing at 40° C. The conversion rate was calculated from the monomer consumption rate by gas chromatography and was found to be 52%. The polyfunctional vinyl aromatic copolymer obtained had an Mn of 1200 and an Mw / Mn of 5. It was also confirmed that the polyfunctional vinyl aromatic copolymer obtained was soluble in toluene, methyl ethyl ketone, tetrahydrofuran, and propyl acetate.
[0049] Synthesis Example 2 (Comparison) Synthesis of polyfunctional vinyl aromatic copolymer B 1.5 kg of toluene was placed in a 5L reaction vessel, and after heating to 40°C, 28 mL of boron trifluoride diethyl ether complex and 1 mL of water were added. Then, a solution of 0.6 kg of DVB-630, 0.7 kg of diisobutylene (mixture of isomers), and 0.02 kg of 1-phenylethanol was added dropwise over 2 hours. Then, the reaction was carried out at 40°C for 9 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed three times with pure water, and polyfunctional vinyl aromatic copolymer B was recovered by degassing at 40°C under reduced pressure. The conversion rate was calculated from the monomer consumption rate by gas chromatography and was found to be 46%. The polyfunctional vinyl aromatic copolymer obtained had an Mn of 800 and an Mw / Mn of 6. It was also confirmed that the polyfunctional vinyl aromatic copolymer obtained was soluble in toluene, methyl ethyl ketone, tetrahydrofuran, and propyl acetate.
[0050] Synthesis Example 3 (Comparison) Synthesis of multifunctional vinyl aromatic copolymer C 0.46 kg of DVB-630, 1.2 kg of styrene, and 1.5 kg of n-propyl acetate were placed in a 5 L reactor, and 54 mL of boron trifluoride diethyl ether complex was added at 70°C and reacted for 4 hours. After the polymerization solution was stopped with an aqueous solution of sodium bicarbonate, the oil layer was washed three times with pure water, and polyfunctional vinyl aromatic copolymer C was recovered by degassing at 40°C. The conversion rate was calculated from the monomer consumption rate by gas chromatography and was found to be 43%. The polyfunctional vinyl aromatic copolymer obtained had an Mn of 2000 and an Mw / Mn of 15. It was also confirmed that the polyfunctional vinyl aromatic copolymer obtained was soluble in toluene, methyl ethyl ketone, tetrahydrofuran, and propyl acetate.
[0051] Example 1 Mixing and hardening A mixture of 50 parts by weight of polyfunctional vinyl aromatic copolymer A as solid content and 50 parts by weight of styryl-modified polyphenylene ether (crosslinking agent A) as a crosslinking agent to make a resin component of 100 parts by weight was added, and 0.5 parts by weight of Perbutyl P as a radical polymerization initiator and 0.2 parts by weight of ADK STAB AO-60 (pentaerythritol tetrakis [3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]) as an antioxidant were added per 100 parts by weight of the resin component. Toluene was then added to make the solid content 50%, thereby obtaining a blended solution. The resulting solution was applied onto a PET film and dried in an oven at 130°C for 10 minutes to obtain a blended film. The resulting film was pulverized into powder, and then cured using a 0.8mm spacer in a vacuum press (KVHC-III manufactured by Kitagawa Seiki) at a temperature of 150°C for 30 minutes, then 200°C for 45 minutes at a pressure of 4MPa to obtain a plate-shaped molded product. The dielectric properties of the molded product were evaluated using the method described above. The glass transition temperature was also measured using the same method as above, after obtaining a molded product using the same method except that the spacer was changed to 2mm.
[0052] Examples 2 to 5, Comparative Examples 1 to 3 The ingredients were mixed in the amounts (parts) shown in Table 1, and the same operations as in Example 1 were carried out to prepare molded products and carry out the same tests. The results are also shown in Table 1.
[0053] [Table 1]
[0054] In Examples 1 to 5, the use of the polyfunctional vinyl aromatic copolymer A resulted in a curable resin composition having a high glass transition temperature and excellent dielectric properties. In Comparative Examples 1 and 2, it was confirmed that the dielectric properties were excellent, but the glass transition temperature was low. In Comparative Example 3, the use of the polyfunctional vinyl aromatic copolymer C that did not contain an α,α-disubstituted olefin compound resulted in a deterioration in the dielectric properties.
Claims
1. (A) Polyfunctional vinyl aromatic copolymer (B) Crosslinking agent (C) Radical Polymerization Initiator The polyfunctional vinyl aromatic copolymer as component (A) satisfies all of the following conditions (1) to (4), and the curable resin composition is characterized in that, when the resin solid content in the resin composition is 100 parts by weight, the amount of component (A) is 5 to 95 parts by weight, the amount of component (B) is 5 to 95 parts by weight, and the amount of component (C) is 0.01 to 10 parts by weight per 100 parts by weight of the resin solid content. (1) containing 0.5 mol % or more and 95 mol % or less of structural units derived from a divinyl aromatic compound (a), 0.5 mol % or more and 75 mol % or less of structural units derived from a monovinyl aromatic compound (b) having no substituent at the α-position, and 5 mol % or more and 75 mol % or less of structural units derived from an α,α-disubstituted olefin compound (c); (2) The number average molecular weight Mn of the polyfunctional vinyl aromatic copolymer is 300 to 100,000, and the molecular weight distribution (Mw / Mn) represented by the ratio of the weight average molecular weight Mw to the number average molecular weight Mn is 100 or less; (3) The monovinyl aromatic compound (b) having no substituent at the α-position is one or more monomers selected from the group consisting of styrene, vinylnaphthalene, vinylbiphenyl, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, m-ethylvinylbenzene, and p-ethylvinylbenzene; (4) The α,α-disubstituted olefin compound (c) is one or more monomers selected from the group consisting of isobutylene, diisobutylene, 2-methyl-1-butene, 2-methyl-1-pentene, 1-methyl-1-cyclopentene, 2-methyl-1-hexene, 1-methyl-1-cyclohexene, 2-methyl-1-heptene, 2-methyl-1-octene, 2-methyl-1-nonene, 2-methyl-1-decene, 2-methyl-1-dodecene, 2-methyl-1-tetradecene, 2-methyl-1-hexadecene, 2-methyl-1-octadecene, 2-methyl-1-eicosene, 2-methyl-1-docosene, 2-methyl-1-tetracosene, and α-methylstyrene.
2. 2. The curable resin composition according to claim 1, wherein the crosslinking agent (B) contains a maleimide structure as a component that causes a crosslinking reaction.
3. 2. The curable resin composition according to claim 1, wherein the crosslinking agent (B) contains a polyphenylene ether structure.
4. 2. The curable resin composition according to claim 1, wherein the crosslinking agent (B) contains a structure derived from a butadiene structure.
5. 2. The curable resin composition according to claim 1, wherein the radical polymerization initiator (C) contains a peroxide structure.
6. 2. The curable resin composition according to claim 1, wherein the radical polymerization initiator (C) contains an azo structure.
7. 2. The curable resin composition according to claim 1, wherein the curable resin composition has a dielectric loss tangent after curing of less than 0.005 at 10 GHz.
8. 2. The curable resin composition according to claim 1, which is in the form of a varnish and contains a solvent in addition to the components (A), (B), and (C).
9. A film comprising the curable resin composition according to claim 1.
10. A prepreg comprising glass cloth impregnated with the curable resin composition according to claim 1.
Citation Information
Patent Citations
Curable composition and cured body of the same
JP2024071737A
Polyfunctional vinyl aromatic copolymer and method for manufacturing same, copolymer rubber obtained therefrom, rubber composition, rubber crosslinked material, and tire member
WO2020067336A1